2007
DOI: 10.1128/iai.00244-07
|View full text |Cite
|
Sign up to set email alerts
|

Unique Gene Expression Profiles in Infants Vaccinated with Different Strains ofMycobacterium bovisBacille Calmette-Guérin

Abstract: Vaccination with Mycobacterium bovis bacille Calmette-Guérin (BCG) has variable efficacy in preventing tuberculosis. We hypothesized that some of this variation might be due to differences among BCG strains. To test this, neonates in Orizaba, Mexico, were vaccinated with one of three different BCG strains (BCG-Brazil It is estimated that approximately one-third of the world's population is infected with Mycobacterium tuberculosis, with 8 million new cases and nearly 3 million deaths occurring annually (30,38).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 49 publications
1
44
0
3
Order By: Relevance
“…By contrast, the impact of immunizing with various live attenuated vaccine strains (including different BCG preparations) is unclear. Although different BCG strains have been shown to induce unique immune responses in animal models and humans, both preclinical study results and data from clinical trials have strongly suggested that different BCG preparations usually yield similar levels of protection when given at equivalent doses by the same route of administration (4,40,42). In fact, we have shown that the BCG Pasteur and SSI BCG strains induce statistically indistinguishable protective responses against the M. tuberculosis HN878 and M. tuberculosis Erdman strains (S. Derrick, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the impact of immunizing with various live attenuated vaccine strains (including different BCG preparations) is unclear. Although different BCG strains have been shown to induce unique immune responses in animal models and humans, both preclinical study results and data from clinical trials have strongly suggested that different BCG preparations usually yield similar levels of protection when given at equivalent doses by the same route of administration (4,40,42). In fact, we have shown that the BCG Pasteur and SSI BCG strains induce statistically indistinguishable protective responses against the M. tuberculosis HN878 and M. tuberculosis Erdman strains (S. Derrick, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have been proposed to explain the variation in BCG efficacy throughout the world, including differences in dose (10), strains of BCG vaccine (11)(12)(13), age of vaccination (14), methodological practices (10,15), and genetic factors (16). However, one widely accepted hypothesis is that natural immunity to nontuberculous mycobacteria (NTM) in the environment renders BCG vaccine less effective or masks its protective effect (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In addition, diVerential immunogenicity of BCG Japan was also reported. Vaccination with BCG Japan resulted in greater secretion of Th1 cytokines such as IFN-, TNF-, and IL-2, when compared with BCG Danish-vaccinated infants [30], while Wu reported that BCG Japan-vaccinated infants had a signiWcantly greater expression of proinXammatory cytokines in PBMC, such as IL-1, IL-1 , IL-6, and IL-24, than BCG Denmark or BCG Brazil did [31]. Taken together, we can conclude that the discrepancy of above results about immunogenicity and Fig.…”
Section: Discussionmentioning
confidence: 99%